Treatment of elbow instability: state of the art. Issue 2 (15th December 2020) - Marinelli, Alessandro; Graves, Benjamin R; Bain, Gregory Ian; Pederzini, Luigi
Abstract : The elbow is a congruent joint with a high degree of inherent stability, provided by osseous and soft-tissue constraints; however, when substantial lesions of these stabilising structures happen, instability of the elbow occurs. Significant improvements in surgical elbow instability diagnosis and treatment have been recently introduced both for acute and chronic cases. Specific stress tests, recently introduced in the clinical practice, and different imaging techniques, both static and dynamic, allow assessment of the elbow stabilisers and detection of the instability direction and mechanism even in subtle forms. Many surgical techniques have been standardised and surgical instruments and devices, specifically dedicated to elbow instability treatment, have been developed. Specific rehabilitation protocols have been designed to protect the healing of the elbow stabilisers while minimising elbow stiffness. However, despite the progress, surgical treatments can be challenging even for expert surgeons and the rate of persistent instability, post-traumatic arthritis, stiffness and pain can be still high especially in most demanding cases. The biology of the soft-tissue healing remains one of the most important aspects for future investigation. If future research will help to understand, correct or modulate the biological response of soft-tissue healing, our confidence in elbow instability management and the reproducibility of our treatment will tremendously improve. In this paper, the state of the art of the current knowledge of elbow instability is presented, specifically focusing on modern surgical techniques used to solve instability, with repair or reconstruction of the damaged elbow stabilisers.